2013
DOI: 10.1037/a0025911
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of the Race-Based Traumatic Stress Symptom Scale: Assessing the emotional impact of racism.

Abstract: The paper describes the development of the Race-Based Traumatic Stress Symptom Scale (RBTSSS), a measure designed to assess the psychological and emotional stress reactions to racism and racial discrimination. Scale items were derived from existing measures of race-related stress and models of trauma, and were tested on a 330 racially heterogeneous (e.g., Blacks, White, Asian, and Hispanic) adult sample. Exploratory Factor Analyses with oblique rotations revealed a 52-item measure consisting of seven scales; D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
160
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 33 publications
4
160
0
2
Order By: Relevance
“…Racism is involved in many aspects of daily living and is a common experience in the United States (Bonilla‐Silva, ; Carter et al, ; DeLilly, ; Nadal, ; Nadal, Griffin, Wong, Hamit, & Rasmus, ; Nadal et al, ; Shams, ). Tynes et al () stated that there has never been a time in history where racial discrimination has been more critical.…”
mentioning
confidence: 99%
“…Racism is involved in many aspects of daily living and is a common experience in the United States (Bonilla‐Silva, ; Carter et al, ; DeLilly, ; Nadal, ; Nadal, Griffin, Wong, Hamit, & Rasmus, ; Nadal et al, ; Shams, ). Tynes et al () stated that there has never been a time in history where racial discrimination has been more critical.…”
mentioning
confidence: 99%
“…Many researchers (Franklin 2004, Franklin, Franklin, and Kelly 2006; Klonoff and Landrine 1999; Klonoff, Landrine, and Ullman 1999; Pieterse and Carter 2007) have suggested that exposure to discrimination results in psychological distress. However, diagnosing individuals who have encountered discrimination due to race or sexual orientation as having a psychiatric disorder may be an error; symptoms consistent with psychiatric diagnoses may actually be reactions in response to discrimination and not psychiatric abnormalities (Carter et al 2013). In addition, psychiatric diagnoses may lead to individual treatment strategies that ignore the systemic, environmental and institutional factors of racism and heterosexism (Carter et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…RBTSSS . On the RBTSSS (Carter et al, 2013), respondents describe in their own words three memorable race‐based events and select the most memorable to respond to a set of 52 psychological symptom items. Each item is preceded by the statement “As a consequence of the memorable encounter I had with racism.” Responses are scored on a 5‐point Likert‐type scale ranging from 0 ( does not describe my reaction ) to 4 ( this reaction would not go away ).…”
Section: Methodsmentioning
confidence: 99%
“…On the RBTSSS (Carter et al, 2013), respondents describe in their own words three memorable race-based events and select the most memorable to respond to a set of 52 psychological symptom items. Each item is preceded by the statement "As a consequence of the memorable encounter I had with racism."…”
Section: Rbtsssmentioning
confidence: 99%
See 1 more Smart Citation